Morphologic characterization of six parental varieties of yacón (Smallanthus sonchifolius) and thirteen crosses obtained from a hybridization plan - Vegas Albino, Diana P. (2015)
The aim of this study is to characterize morphologically the parental and plants and those obtained from the diallel crosses, to identify the variety obtained and to confirm the hybrid nature of these. Three morphological descriptors of root were used to characterize the parental and 68 of the 162 plants obtained from crosses, each with their replication, in total 834 plants were evaluated. Finally 44 hybrids were obtained, 8 plants with no specific hybridization to no identify if there was cross but inheriting only the characters of the female parent or are replications of this, 9 plants with a non-specific hybrid origin unable to determine whether there was hybridization inheriting shared characters by both parents or single characters of the female parent or not; 7 plants whose male parent is not corresponding to the cross, 2 replications of three hybrids and one replication 1 of 1 of 9 plants with a non-specific hybrid origin also presented a different male parent. The parental V24 showed precocity and the loss of irregular reddish purple specks (anthocyanins indicator) was observed in 44 plants with parental that has this character.